Use of Adjunctive Therapy in Acute Kawasaki Disease in Latin America - Fortuna-Reyna, Brenda; Bainto, Emelia V.; Ulloa-Gutierrez, Rolando; Garrido-García, Luis M.; Estripeaut, Dora; del Águila, Olguita; Gómez, Virgen; Faugier-Fuentes, Enrique; Miño-León, Greta; Beltrán, Sandra; Cofré, Fernanda; Chacón-Cruz, Enrique; et al. (Frontiers in Pediatrics, 2020)
The objective was to characterize the use of adjunctive therapy in Kawasaki disease (KD) in Latin America between January 1st, 2009 and May 31st, 2017. Of these patients, 1152 received only a single dose of IVIG and 266 received additional treatment. Age at onset was similar in both groups (median 2 vs 2.2 years, respectively); the majority were male (58% vs 63.9%) and were hospitalized with the first 10 days of fever (85.1% vs 84.2%). The most common adjunctive therapy administered was steroids for IVIG-resistance, followed by additional doses of IVIG. The use of biologics such as infliximab was limited. KD patients who received adjunctive therapy were more likely to have a lower platelet count and albumin level as well as a higher Z score of the coronary arteries. This is the first report of adjunctive therapies for KD across Latin America. Future studies should address the barriers to therapy in children with acute KD throughout Latin America.